(untitled) (Caderno Espaço Feminino, 2018)
Resumo O presente texto intenta empreender uma reflexão sobre o estado de enfermidade das mulheres durante os séculos, oportunizado por uma educação errônea. Conclui-se que as desigualdades entre mulheres e homens padece da ininterrupta ingerência das construções seculares, e que possíveis desconstruções caminham a passos lentos. Palavras-chave: Relações de gênero. Educação.Â Filosofia. Preconceito. Gender discrimination in education: history edifying inequalities Abstract This text aims to carry out a reflection on the diseased state of women throughout the centuries, favored by erroneous education. As a conclusion, it is possible to say that the inequality between women and men suffers from the uninterrupted interference of secular constructions and that possible deconstructs move at a slow pace. Keywords: Gender relations Education. Philosophy.Â Preconception.